(111) vertical-type two-dimensional hole gas diamond MOSFETs with hexagonal trench structures. (May 2021) - Tsunoda, Jun; Iwataki, Masayuki; Oi, Nobutaka; Morishita, Aoi; Hiraiwa, Astushi; Kawarada, Hiroshi
Abstract: Low-loss power semiconductor devices realize the efficient control and miniaturization of inverters and greatly contribute to the development of power electronics. N-channel vertical-type power semiconductor devices that simultaneously demonstrate a low resistance and high withstand voltage using wide bandgap semiconductors have been developed. However, p-channel vertical power semiconductor devices with characteristics equivalent to those of n-channel devices have not yet been realized. We report a p-channel vertical-type two-dimensional hole gas (2DHG) diamond metal-oxide-semiconductor field-effect transistor (MOSFET) with a hexagonal trench structure obtained using (111) diamond. The device characteristics of this device are equivalent to those of the vertical-type hexagonal trench power MOSFET obtained using SiC and GaN. The 2DHG can be induced independently of the crystal orientation such that all hexagonal trench sidewalls can be used as the drift layer. The maximum drain current density exceeds 700 mA/mm in a hexagonal trench with a side length of 12 μm, which is the highest value obtained to date for vertical-type diamond MOSFETs. In addition, the maximum drain current density and specific on-resistance standardized in the device active area are 10, 300 A/cm 2 and 4.2 mΩ cm 2, respectively. These results indicate that using (111) diamond is beneficial for vertical-type 2DHG diamond MOSFETs. Graphical abstract: Image 1 Highlights: A p-channel vertical-type 2DHG diamond MOSFET was fabricated. A hexagonal structure was obtained using (111) diamond. The 2DHG can be induced independently of the crystal orientation. The highest reported maximum drain current density was obtained (>700 mA/mm). On-state device characteristics equivalent to an SiC and GaN MOSFET were obtained.